2014
DOI: 10.18632/oncotarget.2279
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient tumor-infiltrating MDSC differentiation system for discovery of anti-neoplastic targets, which circumvents the need for tumor establishment in mice

Abstract: Myeloid-derived suppressor cells (MDSCs) exhibit potent immunosuppressive activities in cancer. MDSCs infiltrate tumors and strongly inhibit cancer-specific cytotoxic T cells. Their mechanism of differentiation and identification of MDSC-specific therapeutic targets are major areas of interest. We have devised a highly efficient and rapid method to produce very large numbers of melanoma-infiltrating MDSCs ex vivo without inducing tumors in mice. These MDSCs were used to study their differentiation, immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…Unlike CD80, CD86 is a co-stimulatory molecule usually associated with immunogenic antigen-presenting cells (APCs) (20), but not with immunosuppressive functioning of MDSCs (21, 22). The tumor-infiltrating Ly6G + / MHCII + cells from WT host expressed low levels of surface CD86.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike CD80, CD86 is a co-stimulatory molecule usually associated with immunogenic antigen-presenting cells (APCs) (20), but not with immunosuppressive functioning of MDSCs (21, 22). The tumor-infiltrating Ly6G + / MHCII + cells from WT host expressed low levels of surface CD86.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the induction of ICD may be one of the mechanisms that underlie the success of adjuvant and neo-adjuvant BC chemotherapy. Moreover, the fact that additional agents used in combinatorial regimens, such as 5-fluorouracil, cyclophosphamide, and taxanes, can boost the immunogenicity of malignant cells 61,86 , or selectively deplete MDSCs and T reg cells [87][88][89] , suggests that the outcome of BC therapy may be-at least partially-linked to the stimulation (or de-inhibition) of tumor-targeting immune responses.…”
Section: Type I Interferonsmentioning
confidence: 99%
“…MDSCs are one such class of cells that can secrete inhibitory cytokines 21, 22 and can differentiate into different heterogeneous populations of myeloid cells that inhibit immune function 23. Previous studies have shown that MDSCs can inhibit the differentiation of effector Th1 cells resulting in immune incompetence and contributing to the development and progression of tumors 24, 25.…”
Section: Discussionmentioning
confidence: 99%